Gender and norms related to an intention for participating in counseling sessions by peer educator - Ira Nurmala; Muthmainnah Muthmainnah; Riris Diana R; Elisa Dwi P (Masyarakat, Kebudayaan dan Politik, 2019)
Nowadays, drugs (narcotics, psychotropic, and addictive substances) abuse gradually increases in the adolescent group, especially High School students. Environmental impact, especially social interaction, gives a high effect on building the character in adolescents. The existence of peer-education activity is one of the promotive and preventive strategies in mitigating drug abuse. This research was done in 10 high schools in Surabaya spread over five regions (Central, North, South, West, and East). This research was quantitative with the cross-sectional design while the data analysis used was a Chi-Square test with a p-value of <0.05 that was based on the significance level. The research finding showed that the intention of student participation was quite high, i.e. 83.1%; from the statistical test, it had been taught that gender had a significant relationship with intention by a p-value of 0.00. Additionally, it had also a relationship with subjective norm by a p-value of 0.00.  Conclusion: the student’s norm has supported their intention to participate in the program. Meanwhile, the research finding that is based on the gender in this research showed that females had a higher intention to participate in the activity than the males had.  Therefore, a conducive environment should be maintained continuously so that the positive norm can motivate the students to participate in the activity held by the peer-educator.